PENGEMBANGAN SISTEM PEMESANAN MAKANAN ONLINE BERBASIS WEBSITE UNTUK MENINGKATKAN EFISIENSI DAN PENGALAMAN PENGGUNA DI INDUSTRI RESTORAN - Dimas Akbar Pramudya; Irfan Ramadhan; Muhammad Habib Rifai (Journal of Research and Publication Innovation, 2024)
The rapid development of technology has an impact on various industries, including the food industry such as restaurants.The purpose of this research is to develop a website-based online food ordering system to improve operational efficiency, order accuracy, and customer data security.This research covers the waterfall development methodology and includes requirements analysis, system design, implementation, testing, and maintenance.The system allows customers to easily order food from anywhere without having to come directly to the restaurant.An attractive and user-friendly interface design was implemented using HTML, CSS, JAVASCRIPT, and PHP. Thorough testing, including trade show attendees on campus, professional testers, and actual users, has shown that the system minimizes administrative errors and provides an optimal user experience. Menu programs such as menu display, payment cart, payment details, and payment confirmation are implemented for customer control and convenience. This implementation is expected to increase customer satisfaction, reduce potential administrative errors, and provide an integrated and effective restaurant online ordering solution. The test results show that the system provides ease of access and control for customers and restaurant staff. The launch of this online ordering site aims to make a positive contribution in supporting the digital transformation of online ordering in the hospitality industry, especially restaurants. Overall, this research successfully created an integrated and effective solution to meet the demands of the digital era in the food industry.